2004
DOI: 10.1002/path.1518
|View full text |Cite
|
Sign up to set email alerts
|

Emmprin, a cell surface inducer of matrix metalloproteinases (MMPs), is expressed in T‐cell lymphomas

Abstract: Degradation of the extracellular matrix by matrix metalloproteinases (MMPs) is a crucial step in tumour invasion and metastasis. In human carcinomas, tumour cell-fibroblast interactions (TFIs) have been demonstrated to play a role in the up-regulation of MMP levels in tumours, and emmprin is a surface molecule on tumour cells that stimulates nearby fibroblasts to produce MMP-1, 2, and 3. T-cell lymphomas frequently show extranodal organ involvement and skin invasion, but a role for TFIs in their invasion has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
62
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 37 publications
1
62
0
1
Order By: Relevance
“…CD147 expression is elevated on several human tumors and has been correlated with the malignancy in some cancers such as primary breast cancer and ovarian cancer, etc. (7)(8)(9)(10)(11)(12). Despite the close correlation between CD147 expression and malignancy of some tumors, it is not clear whether CD147 has a functional role in tumor genesis and hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%
“…CD147 expression is elevated on several human tumors and has been correlated with the malignancy in some cancers such as primary breast cancer and ovarian cancer, etc. (7)(8)(9)(10)(11)(12). Despite the close correlation between CD147 expression and malignancy of some tumors, it is not clear whether CD147 has a functional role in tumor genesis and hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization studies of human surgical specimens have shown that stromal fibroblasts are the predominant source of MMP-2 in most carcinomas (2)(3)(4). Carcinoma cells stimulate nearby fibroblasts to produce MMPs via soluble cytokines and growth factors, or by cell surface interactions mediated by plasma membrane proteins, such as emmprin (5)(6)(7). Emmprin, also called basigin/CD147, is expressed in significantly higher levels in tumor cells than in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Basigin, also known as extracelluar matrix metalloproteinase inducer (EMMPRIN/CD147), is a highly glycosylated member of the immunoglobulin superfamily that is expressed on the surface of many malignant tumor cells and functions as an upstream modulator of matrix metalloproteinase (MMP) production in the local tumor environment (6)(7)(8). Recently, it was demonstrated that Basigin may bind and regulate several tumor-related signalling proteins and stimulate cell proliferation and survival (9).…”
Section: Introductionmentioning
confidence: 99%